Hubungan Pengetahuan dan Tingkat Kecemasan Orang Tua terhadap Vaksinasi Covid-19 pada Anak - Siti Khodijah Nur'Aini Jusuf; Azizah Nurdin; Andi Irhamnia Sakinah; Halimah Sa’diyah (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Introduction: The COVID-19 vaccine is crucial as a preventive measure against infection with the SARS-CoV-2 virus. The Indonesian Pediatric Association (IDAI) has approved the vaccination for children under 12 years, allowing them to receive up to the second dose. However, a lack of knowledge about the vaccine has led to hesitancy among parents, fueled by misinformation and concerns about potential side effects on their children. This study aims to explore the correlation between parental knowledge and their anxiety levels concerning the COVID-19 vaccination for their children.Methods: We conducted a cross-sectional survey with 207 parents of students from SDIT Nurul Fikri in Makassar City. The research instrument was a structured questionnaire. Data were analyzed through univariate analysis, followed by bivariate comparisons using the Chi-square test and multivariate regression.Results: Among the respondents, a majority (58%) exhibited limited knowledge of COVID-19, with 50.2% reporting varying degrees of anxiety about the vaccination for their children. Of the children, 46.3% had received the complete vaccination series. Statistical analysis revealed a significant correlation between parental knowledge and anxiety levels regarding their child’s COVID-19 vaccination (α less than 0.05; p=0.007).Conclusion: There is a significant correlation between knowledge and anxiety concerning children's COVID-19 vaccination, with knowledge being the most significant predictor of anxiety levels.